PENGARUH JUMLAH RUAS PADA PERBANYAKAN DENGAN TEKNIK RUNDUK GULUNG TERHADAP PERTUMBUHAN BIBIT Mucuna bracteata - Sri Murti Tarigan; Hardy Wijaya; Dita P Suwanto (Jurnal Agro Estate, 2020)
Mucuna bracteata is a type of Leguminosae Cover Crop (LCC) which is widely used in Indonesian plantations. The advantage of Mucuna bracteata is that it grows fast. Based on this, a study was conducted to see the rate of difference in the number of internodes planted which could accelerate the growth and development of Mucuna bracteata. The research was carried out in the practical garden area of ​​the Medan Agricultural College of Agribusiness (STIPAP). The research was conducted from May to June 2020. This study used a non-factorial randomized block design (RBD), which consisted of 1 treatment with 4 levels, namely R0 (1 rolled segment), R1 (2 rolled sections), R2 (3 rolled humps), R3 (4 rolled humps) and with 5 repetitions. The results showed that the treatment of R2, namely 3 bundles of rolled knuckles, gave the best effect on the parameter increase in tendril length, namely 89.66 cm, the increase in the number of tendrils, namely 6.38, the increase in the number of leaves, namely 12.50 strands, the increase in the number of segments, namely 11.32 pieces, and the measurement of the root volume, namely 13.00 ml. The treatment of the number of bunded knots had a significant effect on the parameters of tendril length, number of tendrils, number of leaves, number of internodes, and volume of roots.